E-commerce for the Development of Small Medium Enterprises - I Budiarti; A M Akbar (Universitas Komputer Indonesia, 2021)
This study aims to determine the perceived influence of the existence of e-commerce for SMEs and how the development of Small and Medium Enterprises (SMEs) businesses towards e-commerce. This study used descriptive method and literature review with interviews, reading, and quoting. After conducting research on SMEs, it had been proven that with e-commerce, SMEs had become more advanced and increasingly developed. The results of this study were technological advances can be utilized by SMEs to market and develop their business through e-commerce so that many product or service innovations are created.